Finding Erik and Alva: uncovering students who reason additively when multiplying - Larsson, Kerstin (NOMAD Nordic Studies in Mathematics Education, 2016)
This article presents a study in which grade 5 students’ responses to multiplicative comparison problems, a well-known method for distinguishing additive reasoning from multiplicative, are compared to their reasoning when calculating uncontextualised multiplicative tasks. Despite recognising the multiplicative structure of multiplicative comparison problems a significant proportion of students calculated multiplicative problems additively. Therefore, multiplicative comparison problems are insufficient on their own as indicators of multiplicative reasoning.